An Exertion to Alleviate Stitch Defects During Garments Production - Sultana, Mst. Farzana; Akhter, Tahmina; Mridha, Jaglul Hoque (European Scientific Journal, ESJ, 2019)
In garments industry sewing is the most critical phase during an apparel production. Different types of sewing and stitching defects are occured in this phase due to various problems. As today’s world each customer is expecting a very high quality garments with product variety, it has become a very challenging task for garments quality management. Here all the data were collected from Gardenia Wears Limited situated at Barmi- Sreepur, Gazipur, Dhaka and data were analyzed for reducing Defects per Hundred Unit (DHU%) and also top 10 stitch defects were identified and analyzed later. Finally the work shows reduction of DHU% from 5.23% to 3.48% and also reduce the top ten stitch defects with comparison to before trial and after trial data of ten days and it is proved that an industry can achieve higher production capability & profitability with improved quality product and also saving cost due to reducing DHU%.